Transcatheter aortic valve replacement with the VenusA-Pro and VenusA-Plus systems: preliminary experience in China - Li, Jie; Sun, Yinghao; Luo, Songyuan; Zheng, Shengneng; Chen, Jiaohua; Fu, Ming; Fang, Zhenfei; Wang, Yan; Li, Guang; Fan, Ruixin; Luo, Jianfang (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: The outcomes after transcatheter aortic valve replacement (TAVR) with the second-generation retrievable VenusA-Pro and VenusA-Plus delivery systems using self-expanding VenusA-Valve have not been described before. This study aimed to report the outcomes of both second-generation delivery systems. METHODS: From January 2022 to April 2023, patients with severe aortic stenosis undergoing TAVR with VenusA-Pro from 3 centers across China were prospectively included as a first-in-man study and those with VenusA-Plus were retrospectively identified. All outcomes were reported according to Valve Academic Research Consortium 3 definition. Primary outcome was 30-day all-cause mortality. RESULTS: A total of 156 patients were included, 46 with VenusA-Pro and 110 with VenusA-Plus. The median Society of Thoracic Surgeons score was 2.1%, 55.1% were bicuspid anatomy and mean aortic root calcification volume were 693 mm3. The technical success rate was 91.7%, comparable between VenusA-Pro and VenusA-Plus (87.0% vs 93.6%, P = 0.169). The 30-day all-cause mortality was 2.6%, similar between VenusA-Pro and VenusA-Plus (2.2% vs 2.7%, P = 0.842). No myocardial infarction occurred. The incidences of stroke (0.6%), major bleeding (3.8%), major vascular complications (5.1%), acute kidney injury (9.0%), permanent pacemaker implantation (5.1%), new-onset atrial fibrillation (5.8%) and moderate to severe paravalvular aortic regurgitation (6.0%) were favorable and comparable between two groups. The clinical outcomes were similar between bicuspid and tricuspid aortic valve, except that the incidence of permanent pacemaker implantation was lower in bicuspid anatomy (1.2% vs 10.6%, P = 0.010). CONCLUSIONS: The 30-day outcomes of TAVR with VenusA-Pro and VenusA-Plus were favorable and comparable.